Modelo de autoevaluación integrado entre la norma ISO 9004 y el sistema único de acreditación en salud (2012)
Any process of continuous improvement in organizations requires a periodic reflection regarding the path, progress, setbacks and challenges that arise while striving to achieve organizational purposes. Selfassessment, as an internal assessment process, constitutes a valuable tool for conducting such a reflection.The ISO 9004:2009 model of quality management contains a tool to conduct a self-assessment, which identifies opportunities for improvement, shows strengths and weaknesses to achieve sustained success, establishes the level of maturity of the organization and, if repeated, determines the progress of the organization over time; given the general approach of ISO 9004, this tool is applicable to any type of organization.Moreover the Sistema Único de Acreditación for health institutions in Colombia, also includes a self-assessment tool with very high specificity for the health sector, but this does not have the systemic approach of ISO 9004, it is not possible to determine a level of maturity and, according to users, it is complex to implement.The possibility is then perceived of creating a methodological tool that integrates the best of both tools and is practical in application.This paper presents the results of applying the ISO 9004: 2009 model assessment tool in a high level of complexity health servicing institution and its comparison with the result of the self-assessment of the Sistema Único de Acreditación.This exercise identified the similarities, differences, strengths and weaknesses of the two instruments, which led in turn to a complementary orientation and integration of models of quality management, to develop and present a new proposal for an instrument of self-evaluation, enriched and strengthened, applicable to any health institution which wants to opt for accreditation.